ANALISIS PENGGUNAAN APLIKASI LINKEDIN DALAM MEMBANGUN PERSONAL BRANDING PADA MAHASISWA UNIVERSITAS NEGERI GORONTALO MENGGUNAKAN MODEL UTAUT - Lantu, Zulvikry Andre; Kusuma, Ma'rifatul Sasmitha; Ts. Bullah, Ilham; Amali, Lanto Ningrayati (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2026)
Personal branding is an important element for students in shaping their professional image and preparing themselves for the world of work. As a professional social networking platform, LinkedIn offers various features that can support the formation of a professional identity, but its utilization by students is still not optimal. This study aims to examine the strength of the relationship between variables in the UTAUT model and the behavior of using LinkedIn as a means of personal branding among students at Gorontalo State University. Using a quantitative descriptive approach, data was collected through a questionnaire (gfrom) distributed to 80 students who actively use LinkedIn. The analysis was conducted using the PLS-SEM tool with the SmartPLS version 4 application. The results show that Social Influence and Performance Expectancy have an influence on Behavioral Intention with a t-statistic > 1.990 and a p-value < 0.05, while Effort Expectancy does not show a significant influence because the results do not meet the criteria. In addition, Facilitating Condition and Behavioral Intention also had an effect on Use Behavior. UTAUT in this study was able to explain 59.3% of the variance in Behavioral Intention and 58.4% of the variance in Use Behavior. These findings indicate that perceived benefits and environmental support have a stronger influence than ease of use in encouraging students to use LinkedIn.